Eosinophilic Meningitis Caused by Angiostrongylus cantonensis in an Adolescent With Mental Retardation and Pica Disorder - Chang-Wei Hsueh; Huan-Sheng Chen; Chen-Hua Li; Yu-Wei Chen (Elsevier, 2013)
Eosinophilic meningitis or encephalitis is a rare disorder and is most commonly caused by Angiostrongylus cantonensis. Humans are accidentally infected when they ingest raw snails or vegetables contaminated with the parasite larvae. Because of the improvement in sanitary food handling practices, the occurrence of A. cantonensis eosinophilic meningitis has been decreasing in Taiwan in recent decades. The common symptoms and signs of eosinophilic meningitis are severe headache, neck stiffness, paresthesia, vomiting, nausea, and fever. Acute urinary retention is a rare presentation. We report a case of A. cantonensis eosinophilic meningitis in an intellectually disabled patient who presented with acute urinary retention without any other meningeal signs. The patient received supportive treatment with corticosteroid therapy and was discharged and received urinary rehabilitation at home.